IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS AI CANVA TERHADAP KEMAMPUAN KOGNITIF ANAK USIA DINI KELOMPOK A DI TK AL-MUHAJIRIN - Lulu Nadiyah; Irfan Fauzi Rahmat; Andi Ali Kisai (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an interactive learning medium based on AI Canva to improve the cognitive ability of group A early childhood students at TK Al-Muhajirin, Peusing Village, Jalaksana District, Kuningan Regency. This research is a research and development (R&D) study using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were group A students, consisting of an individual trial with three children and a small-group trial with ten children, along with a material expert, a media expert, and the classroom teacher as validators. Data were collected through expert validation questionnaires, child response observation sheets, and semi-structured interviews, then analyzed descriptively using quantitative and qualitative approaches. The results show that the AI Canva-based learning media obtained a mean score of 2.57 (good category) from the material expert, 3.64 (very good category) from the media expert, and a response percentage of 87.69% (very good category) from the group A trial. The implementation of the media also indicated an improvement in children's cognitive ability in learning and problem-solving, logical thinking, and symbolic thinking. These findings indicate that AI Canva-based learning media is valid, practical, and effective for stimulating the cognitive development of early childhood group A students.